2019
DOI: 10.1158/1078-0432.ccr-18-1232
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LEF1-Mediated DCLK1 by Niclosamide Attenuates Colorectal Cancer Stemness

Abstract: Purpose: Niclosamide, an FDA-approved anthelmintic drug, has been characterized as a potent Wnt inhibitor that can suppress tumor growth and cancer stem-like cell (CSC) populations. However, the underlying molecular mechanisms remain poorly understood. This study aimed to examine how Wnt inhibition by niclosamide preferentially targets CSCs.Experimental Design: The mechanistic role of niclosamide in CSC inhibition was examined in public databases, human colorectal cancer cells, colorectal cancer xenografts, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 49 publications
(75 reference statements)
1
62
0
Order By: Relevance
“…Thus, LEF1 is considered a potential therapeutic target for cancer treatment. LEF1 knock-down and suppression using shRNA and small molecules decreased cell growth in high LEF1 expressing cancer cells [17,18]. In this study, we found that LEF1 is highly expressed in A375, A2058, and G361 melanoma but not various lung cancer cells.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Thus, LEF1 is considered a potential therapeutic target for cancer treatment. LEF1 knock-down and suppression using shRNA and small molecules decreased cell growth in high LEF1 expressing cancer cells [17,18]. In this study, we found that LEF1 is highly expressed in A375, A2058, and G361 melanoma but not various lung cancer cells.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, LEF1 is a promising molecular target for cancer treatment. Indeed, several studies have shown that LEF1 silencing attenuates cancer proliferation and induces apoptosis in glioblastoma multiforme (GBM) and colorectal cancer [17,18]. Furthermore, decreased cellular motility and invasiveness have been observed in LEF1 knocked-down colorectal cancer cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…Niclosamide is an FDA-approved anthelmintic drug 124,125 that suppresses multiple CSC signalling pathways, such as the Wnt, Notch, STAT3 and NF-κB pathways. 126 In addition to targeting mitochondria to induce cell cycle arrest, growth suppression, and apoptosis in cancer cells, niclosamide inhibits CSCs, providing further evidence that it represents a promising agent for cancer therapy.…”
Section: Niclosamidementioning
confidence: 99%
“…127,128 Recently, niclosamide was shown to inhibit the CSC population and their self-renewal activity in colorectal cancer (CRC) cells, leading to irreversible destruction of tumour-initiating potential in vivo. 124 In a trial of cisplatin-induced oral CSC enrichment, application of niclosamide suppressed this process. Consequently, ALDH + OSCC cells are more sensitive to cisplatin therapy.…”
Section: Niclosamidementioning
confidence: 99%
“…In addition, Ji et al (2018) revealed that miR-15b by targeting DCLK1 not only repress self-renewal and tumorigenicity of CRC, but also improves sensitivity of cancer cells to chemo/radiotherapy [8]. Recently, it was shown that Niclosamide (an FDA-approved anthelmintic drug) prevents lymphoid enhancer-binding factor 1 (LEF1)-mediated transcription of DCLK1 and this led to attenuate cancer stemness and sensitizes CRC to chemoradiation [14]. Taken together, it seems that inhibition of DCLK1 restores the radiosensitivity of cancer cells and provides a novel target for the treatment of CRC.…”
mentioning
confidence: 99%